Impact of Demographic Factors, Economic Factors, and Social Media Usage on Political Preferences - Ahmad, Salman; Shahzadi, Amber (Governance and Society Review, 2024)
The current study exploredthe impact of demographicfactors, economic factors, and social media usage on political preferences. The study incorporated demographic variables including age, gender, and education level.Regression analysis was used to conduct the current study. Race/ethnicity, income level/employment status, and social media activity were examined as independent variables. Data was collected from150 respondents,which wasinterpreted using SPSS. Thus, analyzing the data collected from a diverse sample, significant effortwas madeto extend the knowledge of constructs used in the current study. Vivid correlation with demographic and/or economical characteristics, frequency of social media platforms usage,and political affiliations would be used to gain important information.